Feasibility and safety of intranasally administered mesenchymal stromal cells after perinatal arterial ischaemic stroke in the Netherlands (PASSIoN): a first-in-human, open-label intervention study. Issue 6 (June 2022) - Baak, Lisanne M; Wagenaar, Nienke; van der Aa, Niek E; Groenendaal, Floris; Dudink, Jeroen; Tataranno, Maria Luisa; Mahamuud, Ubah; Verhage, Cornelia H; Eijsermans, Rian M J C; Smit, Liesbeth S; Jellema, Reint K; de Haan, Timo R; et al.
Summary: Background: Perinatal arterial ischaemic stroke (PAIS) is an important cause of neurodevelopmental disabilities. In this first-in-human study, we aimed to assess the feasibility and safety of intranasally delivered bone marrow-derived allogeneic mesenchymal stromal cells (MSCs) to treat PAIS in neonates. Methods: In this open-label intervention study in collaboration with all neonatal intensive care units in the Netherlands, we included neonates born at full term (≥36 weeks of gestation) with MRI-confirmed PAIS in the middle cerebral artery region. All eligible patients were transferred to the neonatal intensive care unit of the Wilhelmina Children's Hospital. Neonates received one dose of 45–50 × 10 6 bone-marrow derived MSCs intranasally within 7 days of presenting signs of PAIS. The primary endpoints were acute and subacute safety outcomes, including vital signs, blood markers, and the occurrence of toxicity, adverse events, and serious adverse events. The occurrence of unexpected cerebral abnormalities by a repeat MRI at 3 months of age was a secondary endpoint. As part of standard clinical follow-up at Wilhelmina Children's Hospital, we assessed corticospinal tract development on MRI and performed motor assessments at 4 months of age. This study is registered with ClinicalTrials.gov, NCT03356821. Findings: Between Feb 11, 2020, and April 29, 2021, ten neonates were enrolled in the study. Intranasal administration of MSCs was well tolerated in all ten neonates. No serious adverse events were observed. One adverse event was seen: a mild transient fever of 38°C without the need for clinical intervention. Blood inflammation markers (C-reactive protein, procalcitonin, and leukocyte count) were not significantly different pre-administration versus post-administration and, although thrombocyte levels increased (p=0·011), all were within the physiological range. Follow-up MRI scans did not show unexpected structural cerebral abnormalities. All ten patients had initial pre-Wallerian changes in the corticospinal tracts, but only four (40%) patients showed asymmetrical corticospinal tracts at follow-up MRI. Abnormal early motor assessment was found in three (30%) infants. Interpretation: This first-in-human study demonstrates that intranasal bone marrow-derived MSC administration in neonates after PAIS is feasible and no serious adverse events were observed in patients followed up until 3 months of age. Future large-scale placebo-controlled studies are needed to determine the therapeutic effect of intranasal MSCs for PAIS. Funding: Netherlands Organization for Health Research and Development (ZonMw).